ANALISIS USAHATANI JAGUNG PADA PROGRAM AGROPOLITAN DI PROVINSI GORONTALO - Imran, Supriyo; Tolinggi, Wawan K. (Sainstek, 2011)
The feasibility and income farmers household of the agropolitan program in Gorontalo has been analysed with R/C Ratio and analysis of quantative-induktif model of multiple regresi which was using some data survey based interview and observation that consist of sekunder and primary data survey. The survey of secunder data means to get a data was available that relate with the implmentation of agropolitan program in Province Gorontalo. The survey of primary data has done at the farmer of maize to know the income of the farmer house hold. Result of analysis of the maize farming was known R/C ratio of the maize farming in Pulubala Subahstrict 2.60, Wonosari 1.77, Mananggu 1.53, Patilanggio 1.49 Randangan 2.84 and the whole R/C ratio are 2.18 in Province Gorontalo. This mean that the maize farming at the Agropolitan Program with the profit approach was feasible to be expanded. Contribution income of the farmers house hold in Province Gorontalo from maize farming are 64.03%. The thing prove dependence farmer at maize are very high as source income of household.